Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\dfrac{6x^2y^3-2x^2y+6xy}{6xy}\)
\(=\dfrac{6x^2y^3}{6xy}-\dfrac{2x^2y}{6xy}+\dfrac{6xy}{6xy}\)
\(=xy^2-\dfrac{x}{3}+1\)
b) \(\dfrac{4\left(x+y\right)^3}{2\left(x+y\right)}\)
\(=\dfrac{2\left(x+y\right).2\left(x+y\right)^2}{2\left(x+y\right)}\)
\(=2\left(x+y\right)^2\)
c) \(\dfrac{8x^3+27y^3}{2x+3y}\)
\(=\dfrac{\left(2x\right)^3+\left(3y\right)^3}{2x+3y}\)
\(=\dfrac{\left(2x+3y\right)\left[\left(2x\right)^2-2x.3y+\left(3y\right)^2\right]}{2x+3y}\)
\(=4x^2-6xy+9y^2\)
d) \(\dfrac{48x^4y^3-12x^2y^5+6x^2y^2}{3x^2y^2}\)
\(=\dfrac{48x^4y^3}{3x^2y^2}-\dfrac{12x^2y^5}{3x^2y^2}+\dfrac{6x^2y^2}{3x^2y^2}\)
\(=16x^2y-4y^3+2\)
a) (3x+y)(9x2-3xy+y2) = 27x3+y3
b)(2x-5)(4x2+10x+25) = 8x3-125
a)(3x+y)(9x2 -3xy+y2 )=27x3 +y3 |
b)(2x-5)(4x2 +10x+52 )=8x3 -125 |
nho | k |
minh | nhe |
a) (3x +y)( 9x2 - 3xy + y2)
b) (2x - 5)( 4x2 + 10x + 25)
(đề bài này hay đó)
1)
a) x2/ 3xy/ 9y2
b) 3y/ 4x2/ 9y2
2)
a) A= 532 + 2.53.47 +472
= (53+47)2
= 1002 = 10000
b) B= 154 - 152 -1
= (152 - 15)(152 +15) -1
= 210.240-1
=50400 -1
= 50399
c) C= 502- 492+ 482- 472+...+22-12
= (502- 492)+ (482- 472)+...+(22-12)
= [(50-49)(50+49)] + [(48-47).(48+47)] +...+[(2+1)(2-1)]
=50+49+48+47+...+2+1
=(50+1)(50-1)+1/2
=502-1+1/2
=502 /2 =1250
a) Ta có: \(x^3+12x^2+48x+64\)
\(=x^3+3\cdot x^2\cdot4+3\cdot x\cdot4^2+4^3\)
\(=\left(x+4\right)^3\)
b) Ta có: \(x^3-12x^2+48x-64\)
\(=x^3-3\cdot x^2\cdot4+3\cdot x\cdot4^2-4^3\)
\(=\left(x-4\right)^3\)
c) Ta có: \(8x^3+12x^2y+6xy^2+y^3\)
\(=\left(2x\right)^3+3\cdot\left(2x\right)^2\cdot y+3\cdot2x\cdot y^2+y^3\)
\(=\left(2x+y\right)^3\)
d)Sửa đề: \(x^3-3x^2+3x-1\)
Ta có: \(x^3-3x^2+3x-1\)
\(=x^3-3\cdot x^2\cdot1+3\cdot x\cdot1^2-1^3\)
\(=\left(x-1\right)^3\)
e) Ta có: \(8-12x+6x^2-x^3\)
\(=2^3-3\cdot2^2\cdot x+3\cdot2\cdot x^2-x^3\)
\(=\left(2-x\right)^3\)
f) Ta có: \(-27y^3+9y^2-y+\frac{1}{27}\)
\(=\left(\frac{1}{3}\right)^3+3\cdot\left(\frac{1}{3}\right)^2\cdot\left(-3y\right)+3\cdot\frac{1}{3}\cdot\left(-3y\right)^{^2}+\left(-3y\right)^3\)
\(=\left(\frac{1}{3}-3y\right)^3\)
a)(x+3y)(x2-3xy+9y2)=x3+27y3
b)(2x-3y)(4x2+6xy+9y2)=8x3-27y3